2014
DOI: 10.1007/s00213-014-3792-y
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcer devaluation as a consequence of acute nicotine exposure and withdrawal

Abstract: RATIONALE Nicotine discontinuation produces behaviors in rats that are congruent with anhedonia, and these symptoms may be related to the devaluation of non-nicotine reinforcers. OBJECTIVE Four separate experiments were performed to explore the parameters surrounding nicotine-induced reinforcer devaluation. METHODS In Experiments 1 and 2, nicotine (0.1 or 0.3 mg/kg) or 0.3 mg/kg nicotine plus 1.0 mg/kg mecamylamine was delivered to rats prior to progressive ratio (PR) schedule sessions in which sucrose was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…Mecamylamine abolished the nicotine REE at the highest dose tested (1 mg/kg), without altering response rates when given alone. The same overall result has previously been reported with both primary or conditioned reinforcers, studied with higher SC doses (i.e., 0.3-0.6 mg/kg) of nicotine (e.g., Guy and Fletcher 2013;Ivanová and Greenshaw 1997;Kirshenbaum et al 2014;Olausson et al 2004;Palmatier et al 2009). Mecamylamine, given at 1 mg/kg, would likely antagonize a variety of CNS and ganglionic nAChR subtypes (Papke et al 2001) but without inhibiting NMDA-type glutamate receptors (Clarke et al 1994).…”
Section: Individual Drugs and Receptor Targetssupporting
confidence: 76%
See 1 more Smart Citation
“…Mecamylamine abolished the nicotine REE at the highest dose tested (1 mg/kg), without altering response rates when given alone. The same overall result has previously been reported with both primary or conditioned reinforcers, studied with higher SC doses (i.e., 0.3-0.6 mg/kg) of nicotine (e.g., Guy and Fletcher 2013;Ivanová and Greenshaw 1997;Kirshenbaum et al 2014;Olausson et al 2004;Palmatier et al 2009). Mecamylamine, given at 1 mg/kg, would likely antagonize a variety of CNS and ganglionic nAChR subtypes (Papke et al 2001) but without inhibiting NMDA-type glutamate receptors (Clarke et al 1994).…”
Section: Individual Drugs and Receptor Targetssupporting
confidence: 76%
“…For example, enhancement of responding for brain stimulation reward and conditioned sensory reinforcers appears to depend on the participation of α4β2* nicotinic acetylcholine receptors (nAChRs) Spiller et al 2009;Tobey et al 2012) and several other transmitter systems (see Discussion). For primary sensory reinforcers, the focus of the present study, nicotine-induced enhancement is reported to be mimicked by the partial nAChR agonist varenicline (Levin et al 2012), abolished by the nAChR antagonist mecamylamine (Kirshenbaum et al 2014;Liu et al 2007;Palmatier et al 2009), reversed by the opioid antagonist naloxone (Kirshenbaum et al 2016), and unaffected by pretreatment with adrenergic or glutamatergic receptor antagonists (Palmatier et al 2009;Palmatier et al 2007).…”
Section: Introductionmentioning
confidence: 80%
“…In dependent smokers, forced abstinence is associated with diminished reward sensitivity (Dawkins, Powell, et al, 2007; Dawkins, Acaster, et al, 2007; Kalamboka et al, 2009; Lawn et al, 2015; Pergadia et al, 2014; Snuggs & Hajek, 2013), but whether the prolonged nicotine exposure that occurs in dependence is a necessary condition for reward desensitization to occur remains unclear. Unlike tests of the direct reinforcing-enhancement effect of nicotine, experimental evidence of reinforcement devaluation by nicotine (Kirshenbaum et al, 2015) in naïve users would require several nicotine doses over a substantially longer period in which to study nicotine’s aftereffects in the laboratory environment.…”
mentioning
confidence: 99%
“…Most studies to date have focused on the mechanisms and pathophysiology of chronic diseases caused by smoking [ 3 , 4 , 12 ]. However, acute exposure, defined as a single exposure to a harmful substance [ 25 ], is an important issue in adolescents who begin to smoke voluntarily [ 11 ]. Adolescents are more vulnerable to neurobiological changes, mental health, and substance-use disorders, as this period of life is essential for brain development associated with self-control and regulation [ 9 , 46 ].…”
Section: Introductionmentioning
confidence: 99%